2021
DOI: 10.3390/foods10061315
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Analysis of Internal Quality in Pears with a Self-Made Near-Infrared Spectrum Detector Combined with Multivariate Data Processing

Abstract: The consumption of pears has increased, thanks not only to their delicious and juicy flavor, but also their rich nutritional value. Traditional methods of detecting internal qualities (e.g., soluble solid content (SSC), titratable acidity (TA), and taste index (TI)) of pears are reliable, but they are destructive, time-consuming, and polluting. It is necessary to detect internal qualities of pears rapidly and nondestructively by using near-infrared (NIR) spectroscopy. In this study, we used a self-made NIR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
(60 reference statements)
0
4
0
Order By: Relevance
“… Yang et al (2022) and ( Yu et al, 2021b ) determined soluble solids content in pears based on VIS-NIR and model analysis and variable selection. Wu et al (2021) . settled up a non-destructive characterization of pears by a home-made NIR and a chemometric prediction model.…”
Section: Chemometricsmentioning
confidence: 99%
“… Yang et al (2022) and ( Yu et al, 2021b ) determined soluble solids content in pears based on VIS-NIR and model analysis and variable selection. Wu et al (2021) . settled up a non-destructive characterization of pears by a home-made NIR and a chemometric prediction model.…”
Section: Chemometricsmentioning
confidence: 99%
“…Sheng et al (Sheng et al, 2020) used NIR spectroscopy and the uninformative variable elimination algorithm to nondestructively detect the LC in Korla fragrant pear. Wu et al (Wu, Li, & He, 2021) concluded that NIR diffuse reflectance spectroscopy technology combined with frequency and regression coefficient of variables bootstrapping soft shrinkage (FRC‐BOSS) was an accurate and useful tool for the non‐destructive and rapid determination of snow pear LC.…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near-infrared (Vis-NIR) spectroscopy is the most advanced nondestructive technique for fruit quality assessment due to its high repeatability, ease of operation, lack of pollution and measurement stability [13]. NIR, Vis-NIR spectroscopy and hyperspectral imaging have been used to assess soluble solid content, titratable acidity, dry matter and firmness in pears with less or more successful results [14]. Spectroscopic techniques were also used to detect internal browning [15][16][17], to classify pears in different ripening degrees [18] or to predict postharvest shelf-storage time [19].…”
Section: Introductionmentioning
confidence: 99%